O centro educacional unificado (ceu) como espaço de formação do sujeito através da participação em atividades culturais - Silva, Célia Vanderlei da (2014)
This thesis presents the results of research carried out on the participation in cultural activities of people from two communities of the City of São Paulo, where are located two CEUs (Unified Educational Centres) which an entity maintained by the City Council The research objective was to find out how these people see the availability and participation in such cultural activities. The research problem was defined as follows: in the view of the users of these two CEUs, which formative contributions the engagement in cultural activities offered by this equipment were brought to them? The hypothesis that guided the research was that from the moment in which users actively participate in cultural activities offered by these two CEUs, their behaviour change and they become more committed, more humane and sympathetic. Cultural activities offered as well as the turnout of people from both communities were identified and it was sought to know from some of these people what formative contributions their participation brought to them. The theoretical framework of ideas was sourced from Joaquim Antonio Severino with regards to symbolic production inherent to human existence and from Edgar Morin on the importance of culture in the process of human evolution, and in itself the artistic production and fruition. The analysis of participation rates of people from the two communities, as well what they expressed in relation to the benefits to their own lives, allowed to reach the conclusion that it is fundamental to provide access for users to these benefits and for them to participate in their production in the format in which this is done at CEUs . This conclusion confirms our hypothesis that participation or attainment of symbolic cultural benefits offered can be positive factors in the humanisation process of the people involved.